2010
DOI: 10.1007/s10495-010-0500-1
|View full text |Cite
|
Sign up to set email alerts
|

A fibrillar form of fibronectin induces apoptosis by activating SHP-2 and stress fiber formation

Abstract: Fibronectin (FN) is an endogenous ligand of integrins, which plays a critical role in cell adhesion and growth. Here, we converted globular FN (G-FN) into a fibrillar form (F-FN) and found that, even though both G-FN and F-FN interacted with integrin alpha5beta1, G-FN induced cellular proliferation, whereas F-FN resulted in apoptosis that was associated with deactivation of Akt/GSK-3beta and phosphorylation of SHP-2. SHP-2 inhibitor and anti-sense oligodeoxynucleotide decreased SHP-2 level and reversed the F-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…Aggregates are embedded in secreted FN, which makes it possible to both activate α5β1 integrin and phosphorylate FAK on Tyr 397 , thereby producing slower, but detectable, cell proliferation than that of monolayer cultures and preventing anoikis (Hindie et al, 2005). Huang et al (2010) showed that in SKOV‐3 and MCF‐7 cancer cells, globular FN causes proliferation, whereas fibrillar FN triggers apoptosis, even though both types of FN interact with α5β1 integrins. Apoptosis is thus associated with the activation of RhoA/ROCK and the deactivation of Akt/downstream protein GSK‐3β (glycogen synthase kinase‐3β).…”
Section: Discussionmentioning
confidence: 99%
“…Aggregates are embedded in secreted FN, which makes it possible to both activate α5β1 integrin and phosphorylate FAK on Tyr 397 , thereby producing slower, but detectable, cell proliferation than that of monolayer cultures and preventing anoikis (Hindie et al, 2005). Huang et al (2010) showed that in SKOV‐3 and MCF‐7 cancer cells, globular FN causes proliferation, whereas fibrillar FN triggers apoptosis, even though both types of FN interact with α5β1 integrins. Apoptosis is thus associated with the activation of RhoA/ROCK and the deactivation of Akt/downstream protein GSK‐3β (glycogen synthase kinase‐3β).…”
Section: Discussionmentioning
confidence: 99%
“…Further, our own studies recently found that fibrillar bovine serum albumin (F-BSA) induced apoptosis in human breast duct carcinoma cell line T47D, and fibrillar fibronectin (F-FN) induced apoptosis in human breast cancer cell line MCF-7. F-BSA and F-FN induced BHK-21 cell (baby hamster kidney cell) apoptosis through negatively regulating the integrin/FAK/Akt/GSK-3 signaling pathway and activating SHP-2 and RhoA/ROCK (Huang et al, 2009;Huang et al, 2010). Together these results suggest that inhibition of the 1 integrin signaling pathway may provide a promising therapeutic approach to breast cancer metastasis.…”
Section: Surface Membrane Integrins As Potential Drug-discovery Targetsmentioning
confidence: 88%
“…Previously, we demonstrated that F-BSA and F-FN induced apoptosis in the less malignant T47D and MCF-7 breast cancer cell lines, respectively (Huang et al, 2009;Huang et al, 2010). In this study, we examine whether F-HSA induced cytotoxicity in the more malignant breast www.intechopen.com cancer cell lines, TS/A and MDA-MB-231, using a 3-(4,5-cimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT)-colorimetry assay to measure the cell viability (MERCK, Darmstadt, Germany).…”
Section: Effects Of F-hsa On Cell Viabilitymentioning
confidence: 97%
See 2 more Smart Citations